2004
DOI: 10.1038/sj.bjp.0705604
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of boswellic acid‐induced Ca2+ mobilisation and MAPK activation to lipid metabolism and peroxide formation in human leucocytes

Abstract: 1 We have previously shown that 11-keto boswellic acids (11-keto-BAs), the active principles of Boswellia serrata gum resins, activate p38 MAPK and p42/44 MAPK and stimulate Ca 2 þ mobilisation in human polymorphonuclear leucocytes (PMNL). 2 In this study, we attempted to connect the activation of MAPK and mobilisation of Ca 2 þ to functional responses of PMNL, including the formation of reactive oxygen species (ROS), release of arachidonic acid (AA), and leukotriene (LT) biosynthesis. 3 We found that, in PMNL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
44
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 41 publications
0
44
0
Order By: Relevance
“…The most-recognized PTs that act on 5-LO are BAs, and many studies addressed the respective molecular interactions (for detailed review see [153], [156]). BAs with an 11-keto moiety, preferably 3-O-acteyl-11-keto-b-BA (AKBA 89, Table 6) are of particular interest, and AKBA 89 is the most efficient derivative with IC 50 values 1.5 ± 15 mM in intact cells [74], [154], [157], [158], [159]. Studies using isolated 5-LO or other types of cell-free assays showed that AKBA 89 is a direct, non-redox-type 5-LO inhibitor (IC 50 values 8 ± 50 mM) [74], [154], [159].…”
Section: Pentacyclic Triterpenesmentioning
confidence: 99%
See 2 more Smart Citations
“…The most-recognized PTs that act on 5-LO are BAs, and many studies addressed the respective molecular interactions (for detailed review see [153], [156]). BAs with an 11-keto moiety, preferably 3-O-acteyl-11-keto-b-BA (AKBA 89, Table 6) are of particular interest, and AKBA 89 is the most efficient derivative with IC 50 values 1.5 ± 15 mM in intact cells [74], [154], [157], [158], [159]. Studies using isolated 5-LO or other types of cell-free assays showed that AKBA 89 is a direct, non-redox-type 5-LO inhibitor (IC 50 values 8 ± 50 mM) [74], [154], [159].…”
Section: Pentacyclic Triterpenesmentioning
confidence: 99%
“…The discrepancies in the potency of AKBA 89 for 5-LO inhibition (1.5 ± 50 mM) reported from different studies may be due to different experimental settings such as cell type, species and enzyme source (purified 5-LO, crude homogenates). It is obvious that AKBA 89 is more efficient in cell-based than in cell-free assays, suggesting additional actions in the intact cell, namely pro-oxidant activity that may irreversibly inactivate 5-LO [157]. Interestingly, the PT 3-oxotirucallic acid (3-oxo-TA 90), also present in B. serrata, is more efficient on cellfree 5-LO (IC 50 = 3 mM), whereas in intact cells 5-LO product synthesis is even elevated at low concentrations, and a significant higher IC 50 value (15 mM) is evident [160].…”
Section: Pentacyclic Triterpenesmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed recently that boswellic acids are capable of elevating the release of arachidonic acid in human isolated polymorphonuclear leukocytes (PMNL) (Altmann et al, 2004) and platelets (Poeckel et al, 2005). Platelets do not express 5-lipoxygenase but contain the closely related p12-LO that converts arachidonic acid to 12-hydro(pero)xyeicosatetraenoic acid [12-H(P)ETE] (Yoshimoto and Takahashi, 2002).…”
mentioning
confidence: 99%
“…Thus, stimulating properties (Safayhi et al, 2000;Altmann et al, 2002Altmann et al, , 2004Poeckel et al, 2005) and inhibitory effects (Safayhi et al, 1992(Safayhi et al, , 1995Werz et al, 1998;Poeckel et al, 2006) of boswellic acids have been reported for these functions, depending on the cell type and the respective experimental settings. For example, for inhibition of 5-lipoxygenase by AKBA, IC 50 values in the range of 1.5 M (Safayhi et al, 1995) up to 50 M (Werz et al, 1997(Werz et al, , 1998 were determined, but also 5-lipoxygenase stimulatory effects in this concentration range were described previously (Safayhi et al, 2000;Altmann et al, 2004).…”
mentioning
confidence: 99%